2021
DOI: 10.3389/fnins.2021.687973
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease and microRNA-132: A Widespread Pathological Factor and Potential Therapeutic Target

Abstract: Alzheimer’s disease (AD) is a common neurodegenerative disease in the elderly and is the most common type of dementia. AD is mostly gradual onset, and involves slow, progressive mental decline, accompanied by personality changes; the incidence of AD gradually increases with age. The etiology of AD is unknown, although it is currently believed to be related to abnormal deposition of amyloid β-protein (Aβ) in the brain, hyperphosphorylation of microtubule-associated protein tau, and the release of various cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 90 publications
(104 reference statements)
1
18
0
Order By: Relevance
“…miRNAs play critical roles in AD pathology, including modulating Aβ and tau production/function, synaptic plasticity, neuronal growth, apoptosis, and inflammatory response ( 138 ). In AD, disruptions have been noted in several miRNAs, including miRNAs 9, 124, 125b, 132, 146a, and 155, which may have the potential to serve as both biomarkers and therapeutic agents ( 138 , 139 ).…”
Section: Biological Aging Hallmarks Of Cognitive Decline and Adrdmentioning
confidence: 99%
“…miRNAs play critical roles in AD pathology, including modulating Aβ and tau production/function, synaptic plasticity, neuronal growth, apoptosis, and inflammatory response ( 138 ). In AD, disruptions have been noted in several miRNAs, including miRNAs 9, 124, 125b, 132, 146a, and 155, which may have the potential to serve as both biomarkers and therapeutic agents ( 138 , 139 ).…”
Section: Biological Aging Hallmarks Of Cognitive Decline and Adrdmentioning
confidence: 99%
“…A recent review highlighted the potential importance of miR-132, which was previously identified in a study of plasma exosomes of AD patients along with miR-212. 40 However, miR-132 was not able to distinguish MCI and AD patients. 41 Additionally, miRNA molecules are detected in increased abundance and are more stable than higher molecular weight RNA molecules 82 .…”
Section: Mirnasmentioning
confidence: 99%
“…Description Nucleic Acid Source miR-132 40,41 ,miR-212 40 , miR-342-5p 42 , miR-200a-3p 43 , miR-502-3p 43 , miR-142-3p 43 , miR-483-5p 43 , miR-486-5p 43 , miR-30b-5p 43 , miR-34a 44 , miR-146a 44 ncRNAs that consist of 20-22 nucleotide sequences and are important for the regulation of gene expression. Studied most in depth as a biomarker for AD miRNA Plasma miRNA-4422 45 , miR-34c 46 , miR-193b 47 , miR-125b 48,49,50,43 , miR-23a 49 , miR-26b 49 , miR-223 50 , miR22-3p 48,[51][52][53][54] Serum miR-135a 55 , miR-146a 48,53,44,56 , miRNA-9 48,46 , miR-101 46 , miR-34a 44 , miR-29a 44 , miR-29b 44 CSF miRNA-200b-5p 35 Tears tRNA-derived RNA fragments (tRFs) 57,58 composed of 73-90 nucleotides and are primarily responsible for translating the messenger RNA (mRNA) sequence into protein tRNA -5' tRNA halves 59 Serum 51A 60 , BACE1…”
Section: Biomarkersmentioning
confidence: 99%
“…MiR-132 has been linked to several neurophysiological processes such as neuronal differentiation, migration and maturation, synaptic transmission, plasticity, and neuroprotection [ 271 , 272 ]. In particular, it represents one of the most-studied miRNAs in AD and, together with its downstream molecular targets (HDAC3, ITPKB, p250GAP, HNRNPU, PTBP2, and SIRT1), is involved in the regulation of two AD pathological hallmarks: tau and Aβ [ 72 , 73 , 74 , 75 , 76 , 77 , 78 ] ( Table 1 , Figure 2 ).…”
Section: Common Dysregulated Mirnas In Ad Pd and Alsmentioning
confidence: 99%